Analysis of mechanical characteristics of walking and running foot functional units based on non-negative matrix factorization - Bai, Xiaotian; Huo, Hongfeng; Liu, Jingmin (Frontiers in Bioengineering and Biotechnology, 2023)
To explore the characteristics of Non-Negative Matrix Factorization (NNMF) in analyzing the mechanical characteristics of foot functional units during walking and running. Eighteen subjects were recruited, and the ground reaction force curves of each foot region during walking and running were collected using a plantar pressure measurement system. NNMF was used to extract the foot functional units. The differences between the base matrices of walking and running were compared by t-tests, and the differences in coefficient matrices were compared by one-dimensional statistical parameter mapping. (1) Two foot functional units for walking and running while the Variability Accounted For by the matrix exceeded 0.90; (2) In foot functional unit 1, both walking and running exhibited buffering function, with the heel region being the main force-bearing area and the forefoot also participating in partial buffering; (3) In foot functional unit 2, both walking and running exhibited push-off function, with the middle part of the forefoot having a higher contribution weight; (4) In foot functional unit 1, the overall force characteristics of the running foot were greater than walking during the support phase of the 0-20% stage, with the third and fourth metatarsal areas having higher contribution weights and the lateral heel area having lower weights; (5) In foot functional unit 2, compared to walking, the overall force was higher during the beginning and 11-69% stages of running, and lower during the 4-5% and 73-92% stages. During running, the thumb area, the first metatarsal area and the midfoot area had higher contribution weights than walking; in the third and fourth metatarsal areas, the contribution weights were lower than walking. Walking and running can both be decomposed into buffering and push-off foot functional units. The forefoot occupies a certain weight in both buffering and push-off functions, indicating that there may be a complex foot function transformation mechanism in the foot transverse arch. Compared to walking, running completes push-off earlier, and the force region is more inclined towards the inner side of the foot. This study suggests that NNMF is feasible for analyzing foot mechanical characteristics.